RELATION OF RHEUMATIC-LIKE CARDIAC LESIONS OF THE MOUSE TO LOCALIZATION OF GROUP A STREPTOCOCCAL CELL WALLS - Ohanian, S. H. (The Rockefeller University Press, 1969)
Mice injected intraperitoneally with isolated cell wall fragments of Group A streptococci develop a carditis similar to that previously observed in mice injected with crude extracts of this organism. Neither the soluble cytoplasmic components of Group A streptococcal cells nor the nonfragmented cell walls produced carditis in this experimental model. Fluorescein and (125)I-labeled antibodies specific for Group A streptococcal cell wall antigens were used to demonstrate that, for 5 wk after injection, cell wall material is localized around the sites of active lesions in the heart. In addition, the cell wall antigen accumulates in the liver, spleen, mediastinal lymph nodes, and the adjacent loose connective tissue, where it persists for at least 10 wk.